Exploration of Mechanisms of Sacubitril/Valsartan in the Treatment of Cardiac Arrhythmias Using a Network Pharmacology Approach - Zhou, Yu; Rui, Shibao; Tang, Shengxin; Ju, Changlin (Frontiers in Cardiovascular Medicine, 2022)
Significant reductions in the incidence of cardiac arrhythmia (CA) and sudden cardiac death (SCD), along with amelioration of heart failure, have been reported for treatment with Sacubitril/valsartan (SV). However, its anti-arrhythmic mechanism remains unclear. The current study aims to explore the anti-arrhythmic molecular mechanism of SV. The direct protein targets (DPT) of SV were extracted from DrugBank. The protein-protein interaction (PPI) network of SV DPTs was constructed using STRING, and the indirect protein targets (IPTs) were also identified. A search for arrhythmia-related genes was conducted using GeneCards and the Comparative Toxicogenomics Database (CTD). The DTPs, ITPs, and arrhythmia-related genes from the two datasets were combined in a Venn diagram, and the overlapping genes were identified as core target genes. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses identified the top 20 biological processes and signaling pathways related to disease and the therapeutic effects of SV. The renin-angiotensin system, adrenergic signaling in cardiomyocytes, and gap junction pathways are strongly implicated in the effects of SV on CA. In conclusion, our bioinformatics analyses provided evidence pertaining to the possible antiarrhythmic mechanisms of SV and may contribute to the development of novel drugs for CA.